The Role of Human Resources Maintenance in Achieving Organizational Agility - الطائي، محمد عبد حسين حسن; إسماعيل، هادى خليل; سوار، شهاب أحمد خضر (جامعة الموصل - كلية الإدارة والاقتصاد, 2020)
تهدف الدراسة إلى التعرف على تأثير صيانة الموارد البشرية على أنواع الرشاقة التنظيمية (رشاقة الاستشعار، رشاقة صنع القرار، ورشاقة التطبيق) في الجامعات الخاصة / إقليم كردستان العراق. استخدمت الدراسة المنهج الوصفي التحليلي، من خلال استخدام استبيان لجمع المعلومات من أعضاء مجالس الجامعات في (11) جامعة خاصة / إقليم كردستان العراق. تضم عينة الدراسة (91) عضواً في مجالس الجامعات المبحوثة. تم استخدام البرنامج الإحصائي (SPSS. V. 21) لتحليل المعلومات التي تم جمعها وللحصول على نتائج اختبار الفرضيات. وكانت النتائج الرئيسة للدراسة هي أن الجامعات المبحوثة تنفذ صيانة الموارد البشرية في مستويات المتوسطة، وأنها تمارس الرشاقة التنظيمية في مستويات عالية. أثبتت الدراسة أن هناك علاقة إحصائية موجبة ذات دلالة إحصائية بين صيانة الموارد البشرية والرشاقة التنظيمية. وتشير الدراسة أيضًا إلى أن صيانة الموارد البشرية لها تأثير معنوي في الرشاقة التنظيمية في الجامعات المبحوثة. تم تقديم عدد من الاقتراحات التي تركز على أن الجامعات الخاصة تحتاج إلى إيلاء المزيد من الاهتمام لأنشطة صيانة الموارد البشرية لأنها لها تأثير معنوي إيجابي في تحقيق الرشاقة التنظيمية.
The study aims at acknowledging the effect of human resources maintenance on the types of organizational agility (sensing agility, decision- making agility, and acting agility) in the private universities / Kurdistan Region of Iraq. The study has used the analytical descriptive methodology, through using questionnaire to collect information from the members of the universities council in (11) private universities /Kurdistan Region of Iraq. The sample of the study includes (91) members of the university councils. The statistical program (SPSS. V. 21) has been used to analyze the data collected and to get the results of the hypotheses testing. The study found that the surveyed universities are implementing human resources maintenance in medium levels, and they practice the organizational agility in high levels. The study showed a positive correlation between human resources maintenance and organizational agility. The study also indicates that human resources maintenance has a significant impact on organizational agility at the surveyed universities. A number of suggestions were presented to focus on that the private universities need to pay more attention to the human resources maintenance activities as they have a positive impact on achieving organizational agility.
Keywords: إدارة الموارد البشرية -- الإدارة التنظيمية -- القيادة الإدارية -- مؤسسات التعليم العالي -- العراق